2014
DOI: 10.1002/ps.3886
|View full text |Cite
|
Sign up to set email alerts
|

Cyantraniliprole: a valuable tool forFrankliniella occidentalis(Pergande) management

Abstract: Low variation in susceptibility across contemporary populations of F. occidentalis and a lack of cross-resistance to other insecticides indicate that cyantraniliprole is a potential candidate in rotation programmes within an insecticide resistance management strategy. The combined sublethal effect on reproduction will have an important impact on population reduction. Available data indicate that cyantraniliprole is likely to be a valuable tool for managing thrips populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
0
17
1
2
Order By: Relevance
“…However, Grávalos et al tested the same insecticide for Mediterranean strains of Bemisia tabaci and found that the LC 50 values for nymphs from 14 field populations varied from 0.011 to 0.116 mg L −1 , a 10.5‐fold natural variability. Other variations in cyantraniliprole susceptibility were observed in populations of Tuta absoluta (Lepidoptera: Gelechiidae), Bactrocera dorsalis (Diptera: Tephritidae) and Frankliniella occidentalis (Pergande) respectively. The present study found a wide range of variation (6.5‐fold) in the susceptibility of S. litura from different areas where this compound had been introduced only for a short time (Table ).…”
Section: Discussionmentioning
confidence: 95%
“…However, Grávalos et al tested the same insecticide for Mediterranean strains of Bemisia tabaci and found that the LC 50 values for nymphs from 14 field populations varied from 0.011 to 0.116 mg L −1 , a 10.5‐fold natural variability. Other variations in cyantraniliprole susceptibility were observed in populations of Tuta absoluta (Lepidoptera: Gelechiidae), Bactrocera dorsalis (Diptera: Tephritidae) and Frankliniella occidentalis (Pergande) respectively. The present study found a wide range of variation (6.5‐fold) in the susceptibility of S. litura from different areas where this compound had been introduced only for a short time (Table ).…”
Section: Discussionmentioning
confidence: 95%
“…Intensive use of spinosyns has led to resistance, 16,28 but the judicious use of spinosyns through effective resistance management programmes can restore susceptibility. 29 34 They also identified antifeedant effects of cyantraniliprole against F. occidentalis, which should be considered in evaluating cyantraniliprole for use in thrips management programmes. The incidence of TSWV has also been shown to be lower following cyantraniliprole applications, possibly because of its antifeedant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Aristizabal et al (2016) also found that spinosad conserved natural enemies, which matches our laboratory results but is not reflected in our field trial. Despite this, given our efficacy results and those of others, an effective S. dorsalis IPM program may include an initial application of spinosad to reduce pest abundance followed by a high rate application of cyantraniliprole, which provided extended protection through 35 d in the field (Bielza & Guillen 2015;Aristizábal et al 2017).…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, residential lawns treated with chlorantraniliprole had more predatory beetles and beneficial arthropods than those treated with clothianidin, bifenthrin, or chlorpyrifos (Larson et al 2012). Cyantraniliprole, the most recently registered anthranilic diamide labeled for landscape pest control use, effectively controls other insect pests, including several thrips species (Bielza & Guillen 2015;Kodandaram et al 2015).…”
Section: Introductionmentioning
confidence: 99%